Synthesis, in vitro α-amylase activity and molecular docking study of benzoxazole derivatives - Ullah, Hayat; Rahim, Fazal; Uddin, Imad; Khan, Misbah Ullah; Khan, Fahad; Hussain, Amjad; Hussain, Rafaqat; Khan, Shoaib (Chemical Data Collections, 2024)
In current study, an efficient and simple synthesis of phenyl-benzoxazoles derivatives (1–14) were carried out, upon cyclization of 2-aminophenol with substituted aldehyde. All synthesized derivatives were characterized through NMR and HREI-MS spectroscopic techniques. All derivatives showed from excellent to moderate inhibitory potential with IC50 value ranging from 0.80 ± 0.09 to 19.30 ± 0.49 µM as compared to the reference drug acarbose (IC50 = 1.70 ± 0.10 µM). Derivative 9 (IC50 = 0.80 ± 0.09 µM) was the most potent while derivative 10 (IC50 = 1.03 ± 0.03 µM) with stand second most potent one. Structural activity relationship (SAR) was carried out which mainly depend upon nature, position and number of the substituent/s on aryl ring. Molecular docking study was carried out to determine the binding interaction of the most potent derivatives in the active site/s of enzyme.